Design of a New Institutional Arrangement for Education Quality Assurance : Lessons for Chile from International and Local Experience - World Bank (Washington, DC, 2017)
This report seeks to inform the process of design and implementation of institutional reforms related to the development of a new education quality assurance system in Chile. The report is a synthesis report that draws on previous work by The World Bank in the context of a two-year program of technical collaboration with the Government of Chile. As part of this collaboration, the World Bank produced two related reports, including: (i) a comparative report that analyzes the K-12 education quality assurance systems of Ireland, the Netherlands, New Zealand and Scotland to understand how quality assurance functions are distributed across central government institutions; the characteristics of these institutions; and the relationships between them; and (ii) a comparative report that analyzes how these four OECD systems have evolved over time; what lessons emerge from their experience implementing institutional reforms in the past 15 years; and what lessons emerge regarding the exercise of education quality assurance functions. In addition, the report draws on two research papers by local experts analyzing the implementation of institutional reforms in Chile s health and criminal justice sectors, as well as on an analysis of the Chilean Ministry of Education s current organizational and human resources capabilities conducted by Ministry of Education staff.